Determination of Sustainability Indicators of Nut Farms: The Case of Pistachio - Belma Doğan Öz; Gamze Saner (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to determine the indicators used to determine the sustainability levels of nut farms and to establish a set of indicators that can be used to measure the level of sustainability of pistachio farms, based on the literature review. As a result of the literature review, among the indicators commonly used to measure agricultural sustainability, a total of thirty sub-criteria were identified, including fifteen sub-criteria for the economic aspect (farm size, yield, etc.), six sub-criteria for the environmental aspect (pesticide, fertilizer, water, energy usage, etc.) and nine sub-criteria for the social aspect (farmer’s age, education, etc.) which can be used in evaluating the sustainability of pistachio cultivation. According to this study's findings, although the theoretical principles, dimensions, and goals of agricultural sustainability are globally adaptable, the applicability of the indicators may vary between regions and countries due to geographic, climatic, and socio-cultural differences. Therefore, the sustainability assessment process requires special attention. Sufficient knowledge and expertise are required in setting goals, selecting indicators, and verifying indicators.